Influence of climate on radial growth of Abies pindrow in Western Nepal Himalaya - Thapa, U K; Shah, S K; Gaire, N P; Bhuju, D R; Bhattacharyya, A.; Thagunna, G. S. (Banko Janakari, 2016)
This study aims to understand the influence of climate on radial growth of Abies pindrow growing in the plateau of mixed forest in Khaptad National Park in Western Nepal Himalaya. Based on the dated tree-ring samples, 362-year long tree-ring width chronology was developed dating back to 1650. The studied taxa of this region was found to have dendroclimatic potentiality that was evident from the chronology statistics calculated. The tree-ring chronology was correlated with climate (temperature and precipitation) data to derive the tree-growth climate relationship. The result showed significant negative relationship with March-May temperature and positive relationship with March-May precipitation. This indicates that the availability of moisture is the primary factor in limiting the tree growth. Banko Janakari, Vol. 23, No. 2, 2013